The Tidal Disruption Event AT2021ehb: Evidence of Relativistic Disk Reflection, and Rapid Evolution of the Disk-Corona System - Yao, Yuhan; Lu, Wenbin; Guolo, Muryel; Pasham, Dheeraj R.; Gezari, Suvi; Gilfanov, Marat; Gendreau, Keith C.; Harrison, Fiona; Cenko, S. Bradley; Kulkarni, S. R.; Miller, Jon M.; Walton, Dominic J.; et al. (Astrophysical Journal, 2022)
We present X-ray, UV, optical, and radio observations of the nearby (approximate to 78 Mpc) tidal disruption event AT2021ehb/ZTF21aanxhjv during its first 430 days of evolution. AT2021ehb occurs in the nucleus of a galaxy hosting a approximate to 10(7) M-circle dot black hole (M-BH inferred from host galaxy scaling relations). High-cadence Swift and Neutron Star Interior Composition Explorer (NICER) monitoring reveals a delayed X-ray brightening. The spectrum first undergoes a gradual soft -> hard transition and then suddenly turns soft again within 3 days at delta t approximate to 272 days during which the X-ray flux drops by a factor of 10. In the joint NICER+NuSTAR observation (delta t= 264 days, harder state), we observe a prominent nonthermal component up to 30 keV and an extremely broad emission line in the iron K band. The bolometric luminosity of AT2021ehb reaches a maximum of 6.0(-3.8)(+10.4)%L(Edd )when the X-ray spectrum is the hardest. During the dramatic X-ray evolution, no radio emission is detected, the UV/optical luminosity stays relatively constant, and the optical spectra are featureless. We propose the following interpretations: (i) the soft -> hard transition may be caused by the gradual formation of a magnetically dominated corona; (ii) hard X-ray photons escape from the system along solid angles with low scattering optical depth (similar to a few) whereas the UV/optical emission is likely generated by reprocessing materials with much larger column density-the system is highly aspherical; and (iii) the abrupt X-ray flux drop may be triggered by the thermal-viscous instability in the inner accretion flow, leading to a much thinner disk.
CRIS-Team WoS Importer:2022-09-30